2020
DOI: 10.1186/s13063-019-4040-x
|View full text |Cite
|
Sign up to set email alerts
|

Treating impulsivity with probiotics in adults (PROBIA): study protocol of a multicenter, double-blind, randomized, placebo-controlled trial

Abstract: Background: Impulsivity and compulsivity are related to emotional and social maladjustment and often underlie psychiatric disorders. Recently, alterations in microbiota composition have been shown to have implications for brain development and social behavior via the microbiota-gut-brain axis. However, the exact mechanisms are not fully identified. Recent evidence suggests the modulatory effect of synbiotics on gut microbiota and the contribution of these agents in ameliorating symptoms of many psychiatric dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…The authors found the incidence of these neuropsychiatric disorders to be 17% in the control group of 35 children and zero in the experimental group of 40 children who received the early probiotic intervention (with about half of the sample lost to attrition during the long follow‐up period). Interestingly, one of the first double‐blind, randomized, placebo‐controlled research projects has recently been launched to test the effects of probiotics on impulsivity in adults with ADHD (Arteaga‐Henriquez et al, 2020).…”
Section: Integrating the Gut Microbiome Perspective Into Criminologic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found the incidence of these neuropsychiatric disorders to be 17% in the control group of 35 children and zero in the experimental group of 40 children who received the early probiotic intervention (with about half of the sample lost to attrition during the long follow‐up period). Interestingly, one of the first double‐blind, randomized, placebo‐controlled research projects has recently been launched to test the effects of probiotics on impulsivity in adults with ADHD (Arteaga‐Henriquez et al, 2020).…”
Section: Integrating the Gut Microbiome Perspective Into Criminologic...mentioning
confidence: 99%
“…Thus, given the evidence presented above that the gut–brain axis likely plays a role in determining aggressive behavior (Sherwin et al, 2019; Sylvia et al, 2019) and that dietary supplementation is one of the most effective ways to influence the microbiome (Carmody et al, 2015; Gentile & Weir, 2018; Zmora et al, 2019), it may be surprising that so few studies test this relationship in humans (the rare exceptions are Arteaga‐Henríquez et al, 2020; Gao et al, 2019; Kato‐Kataoka et al, 2016). Part of the reason for this scarcity of studies must be the fact that the market of probiotics and prebiotics is diverse and largely unregulated (Quigley, 2019), due to the status of being “not quite a medicine.”…”
Section: Possibilities For Randomized Controlled Trials: Establishing...mentioning
confidence: 99%
“…Interestingly, in 2019 a promising multinational clinical trial has been started to evaluate the effect of the administration of a symbiotic formula (Synbiotic 2000 Forte 400) containing a mixture of different probiotics ( Pediococcus pentosaceus , Lactobacillus paracasei subsp. Paracasei , L. plantarum , and Leuconostoc mesenteroides ) and four prebiotics (β-glucan, inulin, pectin, and resistant starch) in a cohort of 180 adults with ADHD [ 219 ]. To date, clinical studies applying probiotics in ADHD patients are still limited and future studies are needed to achieve sufficient evidence to recommend probiotics administration as beneficial treatment in ADHD.…”
Section: Probiotics and Use Of Probiotics In Nddsmentioning
confidence: 99%
“…In this respect, some contributions are expected in the contexts of cognition, emotion and behavior by using probiotic supplements. Some studies suggested that probiotic supplementation in adults was used for the effective treatment of impulsivity, which is the underlying mechanism of certain psychiatric disorders or problem behaviors (Arteaga-Henríquez et al 2020). It is thought that probiotics have important contributions not only in impulsivity but also in the above-mentioned mechanisms.…”
Section: Connections Between Gut Microbiota and Impulsivitymentioning
confidence: 99%